Μακεδονικά Επιγραφικά IV (Θεσσαλονίκη) - Νίγδελης Παντελής Μ. (Tekmeria, 2013)
This article contains corrections, restorations and comments concerning various inscriptions of Thessaloniki and its territory that appeared in dispersed publications following Ch. Edson’s edition of IG X 2.1 (Inscriptiones Thessalonicae et viciniae) in 1972.